Nandrolone excretion is not increased by exhaustive exercise in trained athletes - Schmitt, N.; Flament, M. M.; Goubault, C.; Legros, P.; Grenier-Loustalot, M. F.; Denjean, A. (Medicine & Science in Sports & Exercise, 2002)
PURPOSE The anabolic steroid nandrolone is widely used as a performance enhancer. Traces of its naturally occurring metabolite 19-norandrosterone (19-NA) have been found in human urine (below 0.6 ng.mL ), and it has been suggested that strenuous exercise may increase urinary 19-NA. The aim of our study was to assess the effect of exhaustive exercise on the nandrolone excretion under controlled conditions in two groups of trained male athletes, one composed of judoka and the other of long-distance runners.METHODS A Wingate test and a treadmill limited-time test (running at 85% OV0312;O ) were carried out on 14 judoka and 15 athletes. Hydration was controlled during each session. Urine samples were obtained before each test and 30 min, 60 min, and 24 h after each test. Urinary 19-NA concentrations were determined using gas chromatography coupled with mass spectrometry.(2max)RESULTS Baseline urinary 19-NA concentrations varied widely across individuals, from undetectable levels to 0.250 ng.mL (mean, 0.048 +/- 0.050 ng.mL ). The both exercise tests did not significantly modified urinary 19-NA levels in the two groups of subjects.CONCLUSION Our study provides compelling evidence that endogenous nandrolone production in male athletes, during two very different types of exercise, produces urine levels far below the IOC threshold of 2 ng.mL urine. Thus, exercise does not induce endogenous nandrolone secretion.